Strategi Propaganda dalam Iklan Shopee Belanja Seru, Hidup Lebih Mudah - Raden Dehana Balqis; Arfian Suryasuciramdhan; Vivi Valentine; Cecinia Siburian (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The growth of digital platforms has driven significant transformations in marketing communication strategies, particularly in e-commerce advertising practices. Shopee, as one of the largest e-commerce companies in Indonesia, utilizes digital propaganda strategies through visual and audio content to shape consumer perception and behavior. The advertisement with the slogan "Belanja Seru, Hidup Lebih Mudah" (Fun Shopping, Easier Life) not only conveys promotional messages but also constructs social meanings of consumption, convenience, and happiness through symbols and visual narratives. This study employs a descriptive qualitative method using literature review techniques to analyze the message structure and communication strategies embedded in Shopee advertisements. The analysis considers visual, symbolic, and repetitive elements that function as covert propaganda mechanisms. The theoretical framework is based on propaganda communication and semiotic theory to understand how advertisements systematically shape consumerist consciousness. Findings reveal that propaganda in Shopee’s advertisements operates through symbolic repetition, celebrity endorsement, and the use of digital features such as limited-time promotions that trigger impulsive behavior. These practices contribute to the formation of digital consumer culture, supported by emotional engagement and algorithmic targeting. Media literacy enhancement is therefore essential to equip the public with critical awareness towards persuasive messages in digital spaces.